Tree-ring lignin proxies in Larix gmelinii forest growing in a permafrost area of northeastern China: temporal variation and potential for climate reconstructions - Lu, Qiangqiang; Liu, Xiaohong; Anhäuser, Tobias; Keppler, Frank; Wang, Yabo; Zeng, Xiaomin; Zhang, Qiuliang; Zhang, Lingnan; Wang, Keyi; Zhang, Yu (Ecological indicators, 2020)
The hydrogen and carbon stable isotope ratios (δ2HLM and δ13CLM values) of tree-ring lignin methoxy groups have recently been recognized as valuable palaeoclimate indicators. However, the environmental factors but also sample preparation processes that might cause variations of δ2HLM and δ13CLM values have been not fully explored. Furthermore, the temporal dynamics of wood lignin content on both isotopes hasn’t been investigated. To investigate the effects of total lignin content, removal of lipids and differences between individual and pooled tree-ring series on isotopic values, we analyzed ring samples of dominant Larix gmelinii trees from a typical permafrost region of northeastern China. We also examined relationships between δ2HLM and δ13CLM values with annual-resolution lignin content and climatic parameters over the common period of overlap 1901 to 2013. We found that the inter-tree variability between the individual and pooled isotopic chronologies was consistent, and the removal of lipids did not change the results of stable isotope measurements. The total lignin content shifted between the heartwood and sapwood, whereas the content of guaiacyl monomers (G-lignin), the only donor of methoxy groups, remained constant. Correlations analysis between lignin proxies and climate variables indicated that the heartwood total lignin content was positively correlated with the intrinsic water-use efficiency, temperature and vapor-pressure deficit (VPD), but negatively with the early-growing-season standardized precipitation evaporation index. Whilst δ2HLM values were positively correlated with the growing season temperature (May to August) and VPD, particularly in August, δ13CLM series showed insignificant correlation. Therefore, we suggest that the total lignin content and δ2HLM values of tree rings (both individual and pooled series) are suitable for tracking environment dynamics, as they can reveal the climate responses of tree growth.